Hybrid vibrating wire piezometer–packer system: design verification and underground trial at Carrapateena mine - Young, L.; Ghelichzadeh, J.; Stryk, A. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Backfilling deep exploration boreholes intersecting artesian zones in underground hard rock mines is challenging because high inflow rates can wash out cementitious grout before it sets and potentially displace adjacent groundwater monitoring sensors. To address this issue, a hybrid vibrating wire piezometer–packer system (HVWPPS) was developed by combining a sacrificial inflatable borehole packer with a high-capacity vibrating wire piezometer (VWP), housed within the lower part of the packer assembly. Following laboratory trials, the HVWPPS was deployed at BHP’s Carrapateena underground mine in South Australia, at a depth of 192 m below the borehole collar. The HVWPPS was installed above an artesian dyke feature and inflated to ~9,000 kPa to seal off the artesian zone while allowing water pressures to be accurately measured below the packer. The borehole above the packer was then backfilled using a customised cement-bentonite grout. VWP monitoring at 30-second intervals captured the key steps of installation, including packer inflation, grout placement, packer deflation and the subsequent water pressure response. After approximately six days of grout curing, the packer was fully deflated with no significant pressure drop observed, indicating effective sealing above the packer while groundwater pressure below the packer continued to be measured. This trial demonstrates that the HVWPPS is a practical approach for deep borehole backfilling and continuous pore pressure monitoring in the artesian zones of underground mines.